Implementasi Sistem Informasi Manajemen Berbasis Cloud Computing untuk Memperbesar Daya Saing Organisasi - Istiqomah Istiqomah; Muhammad Irwan Padli Nasution (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
In today's digital era, organizations face the challenge of enhancing their competitiveness in an increasingly competitive environment. One solution adopted is the implementation of Cloud Computing-based Management Information Systems (MIS). This article discusses the implementation of Cloud Computing-based Management Information Systems. This research aims to explore the impact of adopting cloud-based MIS on enhancing organizational competitiveness. Cloud-based MIS allows for the management of data and applications through internet infrastructure, offering flexibility, scalability, and operationasl efficiency. By adopting this technology, organizations can access information in real-time from various locations, support employee mobility, and strengthen strategic decision-making. This research also explores the challenges and benefits faced by organizations during the transition to cloud-based systems and provides recommendations for successful implementation. Key steps in this process include phased implementation, performance monitoring, security evaluation, and integration with existing systems. Cloud-based MIS can provide significant advantages in terms of operational cost reduction, increased flexibility, and the ability of organizations to respond quickly to market changes. However, challenges related to data security and system control must also be considered. Therefore, an appropriate implementation strategy is crucial to ensure the successful adoption of cloud-based MIS.